2015
DOI: 10.3923/ajbkr.2015.46.59
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Plantlet Regeneration System from Nodal, Internodal and Leaf Explants of Sauropus androgynus (Sweet Shoot)

Abstract: Propagation of Sauropus androgynus (SA) by tissue culture technology provides a better alternative than conventional propagation, as it ensures uniformity in production of sustainable plantlets with desirable traits. The objective was to establish an efficient plant regeneration protocol using leaf, nodal and internodal explants of SA, starting from the establishment of aseptic cultures to the acclimatization stage of plantlets. The effects of plant growth regulators on the growth performance of SA were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The present research confirmed the applicability of nodal segments in the in vitro studies with bleeding heart, as all of them demonstrated some type of morphogenetic response, such as caulogenesis, rhizogenesis, callogenesis, and/or embryogenesis. The suitability of this explant type was also reported by We et al (2015), with Sauropus androgynus (L.) Merr. In their research, nodal segments produced a comparable number of adventitious shoots (7.8) as internodes (5.5) and leaf segments (10.0), in the same culture conditions.…”
Section: Discussionsupporting
confidence: 64%
“…The present research confirmed the applicability of nodal segments in the in vitro studies with bleeding heart, as all of them demonstrated some type of morphogenetic response, such as caulogenesis, rhizogenesis, callogenesis, and/or embryogenesis. The suitability of this explant type was also reported by We et al (2015), with Sauropus androgynus (L.) Merr. In their research, nodal segments produced a comparable number of adventitious shoots (7.8) as internodes (5.5) and leaf segments (10.0), in the same culture conditions.…”
Section: Discussionsupporting
confidence: 64%
“…Mean comparison showed an average growth index of shoots significantly varied with BA 1 Kn 0.1 (M3) (Table 1). The higher concentration of BA promotes the development of shoot cultures and increases the number of shoots [25,26]. Green pigment estimation was done in the fresh green leaves samples and shoot cultures of S. androgynus in BA 1 Kn 0.1 medium extracted with methanol.…”
Section: Resultsmentioning
confidence: 99%